Implementation of project-based learning and problem-based learning in mathematics course with students' anxiety: Is it effective? - Pramesti, Getut; Salsabila, Nabila Shafa (Universitas Islam Negeri (UIN) Mataram, 2025)
[English]: Mathematics anxiety often interferes with students’ engagement and achievement, leading to reduced self-confidence and the potential withdrawal from the learning process. Project-Based Learning (PjBL), which emphasizes hands-on, collaborative experiences, is a promising approach for addressing this issue. Meanwhile, problem-solving skills are essential for future learning and Problem-Based Learning (PBL) offers an effective approach to fostering these higher-order thinking skills. This study investigates the effectiveness of PjBL and PBL in enhancing the cognitive performance of students suffering from mathematics anxiety. The study employs quantitative approach with cluster random sampling by targeting 9th-grade students in Banyuasin, East Java, Indonesia. Data were collected through documentation, questionnaires, and achievement tests on spatial geometry, alongside measures of mathematics anxiety. The data was analysed using a one-way covariance (ANCOVA) analysis, treating anxiety as a covariate variable. The findings indicate that both PjBL and PBL significantly enhance students’ learning outcomes despite of their mathematics anxiety (p-value < 0.050). Both approaches promote collaborative learning, peer tutoring, and active student interaction, which foster improved communication skills, reduce anxiety, and deepen mastery of the subject. [Bahasa]: Kecemasan terhadap matematika sering kali mengganggu keterlibatan dan pencapaian siswa, yang menyebabkan penurunan kepercayaan diri dan kemungkinan menarik diri dari proses pembelajaran. Pembelajaran berbasis proyek (PjBL), yang menekankan pada pengalaman aktif serta kolaboratif, merupakan solusi yang menjanjikan untuk masalah tersebut. Sementara itu, kemampuan pemecahan masalah menjadi krusial pada pembelajaran di masa mendatang dan pembelajaran berbasis masalah (PBL) dapat menjadi pendekatan yang dapat meningkatkan kemampuan berpikir tingkat tinggi tersebut. Penelitian ini menguji keefektifan PjBL dan PBL dalam meningkatkan domain kognitif siswa yang mengalami kecemasan matematika. Penelitian ini menggunakan pendekatan kuantitatif dengan pengambilan sampel secara acak kluster yang menargetkan siswa kelas 9 di Banyuasin, Jawa Timur, Indonesia. Data dikumpulkan melalui dokumentasi, angket, dan tes hasil belajar pada materi geometri spasial, bersama dengan pengukuran terhadap kecemasan matematika. Teknik analisis data menggunakan analisis kovariat satu arah, dengan kecemasan sebagai variabel kovariat. Hasil temuan mengindikasikan bahwa PjBL dan PBL meningkatkan hasil belajar siswa dengan kecemasan matematika secara signifikan (p-value < 0.050). Kedua pendekatan tersebut mempromosikan pembelajaran kolaboratif, tutor sebaya, dan interaksi aktif siswa, yang dapat meningkatkan kemampuan komunikasi, mengurangi kecemasan, serta memperdalam penguasaan materi pembelajaran.